2021
DOI: 10.1186/s10194-021-01296-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered speech patterns in subjects with post-traumatic headache due to mild traumatic brain injury

Abstract: Background/objective Changes in speech can be detected objectively before and during migraine attacks. The goal of this study was to interrogate whether speech changes can be detected in subjects with post-traumatic headache (PTH) attributed to mild traumatic brain injury (mTBI) and whether there are within-subject changes in speech during headaches compared to the headache-free state. Methods Using a series of speech elicitation tasks uploaded via… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Based on this analysis, it seems many mTBI patients will experience several disparate psychological issues simultaneously. Our research, which found that conditions associated with speech disorders clustered together with headache symptoms aligns with research showing that mTBI patients experiencing post–traumatic headache experience changes in speech ( 28 ). The clustering of visual disorders, ear disorders, cognitive, and sleep disorders may have occurred because of the physiological nature of mTBI.…”
Section: Discussionsupporting
confidence: 90%
“…Based on this analysis, it seems many mTBI patients will experience several disparate psychological issues simultaneously. Our research, which found that conditions associated with speech disorders clustered together with headache symptoms aligns with research showing that mTBI patients experiencing post–traumatic headache experience changes in speech ( 28 ). The clustering of visual disorders, ear disorders, cognitive, and sleep disorders may have occurred because of the physiological nature of mTBI.…”
Section: Discussionsupporting
confidence: 90%
“…Participants included in this study were enrolled over a period of 3 years (2019–2022). A subset of individuals included in this study were included in a prior publication 7 . However, this is the primary analysis aimed at predicting headache improvement based on clinical questionnaires completed within 0–59 days post‐mTBI.…”
Section: Methodsmentioning
confidence: 99%
“…Pause behavior can also be affected by cognitive and linguistic factors, and increased pausing is associated with TBI and dementia. 18,19,[46][47][48] The speech of fighters was also characterized by more frequent disfluencies. For MT disfluencies (ie, interjections, phrase revisions), fighters produced more than 1 additional disfluency per passage than controls.…”
Section: Discussionmentioning
confidence: 99%